Pediatric Multiple High-Powered Magnetic Buckyballs Ingestion—Experience From Six Tertiary Medical Centers - Ding, Guojian; Liu, Hongzhen; Zhou, Peng; Niu, Qiong; Wang, Wei; Feng, Zhiqiang; Zhang, Shisong; Zhang, Zhengmao; Geng, Lei; Bu, Zhaoyun; Fu, Tingliang (Frontiers in Public Health, 2022)
Multiple high-powered magnetic Buckyball ingestions may lead to a high risk of severe complications. Great concerns have been raised by public health workers, and it remains challenging for clinicians to solve this troublesome problem. We report a large case series of children with Buckyball ingestion from six tertiary medical centers. The clinical data, including demographics, medical history, diagnosis tools, management options, intraoperative or endoscopic findings, and outcomes, were retrospectively analyzed. Seventy-one children aged 1–13 years ingested 2–41 Buckyballs. Among them, Buckyballs passed spontaneously on 2–10 days post-ingestion in seven cases; gastroscopic removal was performed in 14 cases; laparoscopic removal in 13 cases; laparoscopic-assisted surgical removal in 6 cases; and open surgical removal in 31 cases. Surgical indications included small bowel obstruction, perforation, peritonitis, acute abdominal pain, or along with ingestion of other metallic foreign bodies. Among those who underwent a surgical procedure, primary intestinal repair was performed in 44 cases, enterectomy with primary anastomosis in 6 cases. The postoperative hospital stay ranged from 5 to 28 days. No major complications occurred. In unwitnessed cases, a vague medical history and nonspecific symptoms usually make the diagnosis difficult. The treatment options should include the watch-and-wait approach, endoscopic, laparoscopic-assisted, or open surgical removal of Buckyballs, with primary intestinal repair or anastomosis. Preventive measures, including children's not having access to Buckyballs, are essential to protect children from this kind of unintentional injury.